HUBUNGAN PENGETAHUAN HEIMLICH MANUVER PADA IBU DENGAN KETERAMPILAN PENANGANAN ANAK TODDLER YANG MENGALAMI CHOCKING - Edita Refine Siahaan (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2019)
Abstract Introduction: Children at toddler age groups are children who characterized with exploration behavior often experience choking. Choking is a very dangerous emergency situation, mother's knowledge and skills in handling emergency choking is very essential. Purpose: This study aims to explore the characteristics of mother and child, mother's knowledge, and the ability of mothers to handle chocking. Furthermore, this study aims to analyze the relationship between mother's knowledge and the ability to handle chocking. his research is a quantitative study with a research design using cross sectional method. Methods: The population in this study were mothers with children aged 1 to 3 years who were recorded in a satellite health center in Tanjung Raya village, amounting to 50 people. The sample in this study was taken with a total sampling technique. Results: knowledge of mothers with toddlers about Heimlich Maneuver was found to be low. There is a significant relationship between the level of knowledge of mothers with the ability to handle children with p = 0,000. Discussion: the participation of all parties in the health team to increase the knowledge of mothers in handling choking children is very important. Keywords: Knowledge of the mothers, choking among toddler, Heimlich Maneuver